Menelusuri Perjalanan Ilmu Ushul Fiqih Dalam Sejarah - Ichsan Sopyan; Imam Sucipto (An-Nisa: Journal of Islamic Family Law, 2024)
This study examines the historical development of Fiqh and Usul Fiqh as essential branches of Islamic knowledge for establishing Islamic law. Understanding the history of these sciences is crucial to preventing misunderstandings in legal rulings and fostering tolerance in differing opinions. The research employs a qualitative method with a literature review approach, analyzing books, journals, and online sources related to the evolution of Fiqh and Usul Fiqh. The discussion reveals that the development of these sciences can be divided into three main phases. The formative phase (7th to 10th centuries CE) was marked by the application of laws based on the Qur’an, Sunnah, and systematically organized ijtihad by the Prophet, his companions, and the tabi’in. The stagnation phase (10th to 20th centuries CE) saw a decline due to the dominance of taqlid and sectarian fanaticism, although reformist scholars like Ibn Taymiyyah sought to revive the spirit of ijtihad. The developmental phase (post-establishment of national Islamic states) was characterized by the revival of Islamic law through purification movements, legal codifications such as the Majallah al-Ahkam al-‘Adillah, and the adaptation of Fiqh texts to modern contexts. This study concludes that the historical development of Fiqh and Usul Fiqh reflects the dynamic nature of Islamic law, which is adaptable to changing times through cycles of innovation, stagnation, and revival. Understanding this history is essential to maintaining the relevance of Islamic law in addressing modern challenges.